2014
DOI: 10.1287/isre.2013.0511
|View full text |Cite
|
Sign up to set email alerts
|

Online Product Reviews: Implications for Retailers and Competing Manufacturers

Abstract: T his paper studies the effect of online product reviews on different players in a channel structure. We consider a retailer selling two substitutable products produced by different manufacturers, and the products differ in both their qualities and fits to consumers' needs. Online product reviews provide additional information for consumers to mitigate the uncertainty about the quality of a product and about its fit to consumers' needs. We show that the effect of reviews on the upstream competition between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(101 citation statements)
references
References 34 publications
(44 reference statements)
6
95
0
Order By: Relevance
“…On the one hand, if the platform cannot benefit from online reviews, they can establish other policies and rules, just like punitive measures and reputation management, to strengthen supervision and control of low-quality products. On the other hand, if the platform can benefit from online reviews, we conclude the result that the platform always benefits from an improvement in accuracy rates of online reviews is same with the result that was suggested by Young Kwark et al [49]. They can improve the accuracy rate of online reviews to improve their quality and revenue by improving the quality of the voting system and the reputation system or more often providing cash back and return coins.…”
Section: Discussionsupporting
confidence: 86%
“…On the one hand, if the platform cannot benefit from online reviews, they can establish other policies and rules, just like punitive measures and reputation management, to strengthen supervision and control of low-quality products. On the other hand, if the platform can benefit from online reviews, we conclude the result that the platform always benefits from an improvement in accuracy rates of online reviews is same with the result that was suggested by Young Kwark et al [49]. They can improve the accuracy rate of online reviews to improve their quality and revenue by improving the quality of the voting system and the reputation system or more often providing cash back and return coins.…”
Section: Discussionsupporting
confidence: 86%
“…We therefore expand the boundary of CLT's application to a context that offers great potential for studying psychological distance and evaluation. The majority of prior studies on online reviews has focused on understanding the consequences of online reviews, such as facilitating consumer decision making (Hu, Liu, & Zhang, 2008), driving firm sales (Chevalier & Mayzlin, 2006; Zhu & Zhang, 2010) and affecting market competition (Kwark, Chen, & Raghunathan, 2014). Our study, in contrast, examines the antecedents of online review characteristics (e.g., Chen & Kirmani, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Consumers choose to put more emphasis on the realized quality, when the weight on the realized quality, β, is high. A similar weighted average expression can be found in Kwark, Chen, and Raghunathan (), where shoppers' expected quality difference is modeled from two information sources.…”
Section: Extension: a Generalization Of Quality Perception Updatementioning
confidence: 91%